2007
DOI: 10.1096/fj.06-6652com
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D2‐derived phosphatidic acid binds to and activates ribosomal p70 S6 kinase independently of mTOR

Abstract: The product of phospholipase D (PLD) enzymatic action in cell membranes, phosphatidic acid (PA), regulates kinases implicated in NADPH oxidase activation, as well as the mammalian target of rapamycin (mTOR) kinase. However, other protein targets for this lipid second messenger must exist in order to explain other key PA-mediated cellular functions. In this study, PA was found to specifically and saturably bind to and activate recombinant and immunoprecipitated endogenous ribosomal S6 kinase (S6K) with a stoich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 77 publications
3
75
0
Order By: Relevance
“…Exposure of cells to PA resulted in the accumulation of PA inside the cell clustered into discrete patches/vesicles where it can lead to the activation of S6K. Lehman et al (6) have shown immunofluorescent staining of S6K shifting away from perinuclear regions and colocalizing with PLD2 in the cytosol. It is also possible that PA could be on early endosomes during triggered endocytosis and subsequently move into recycling endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of cells to PA resulted in the accumulation of PA inside the cell clustered into discrete patches/vesicles where it can lead to the activation of S6K. Lehman et al (6) have shown immunofluorescent staining of S6K shifting away from perinuclear regions and colocalizing with PLD2 in the cytosol. It is also possible that PA could be on early endosomes during triggered endocytosis and subsequently move into recycling endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, overexpression of recombinant PLD2 has been reported to activate mTORC1 in MCF-7 breast cancer cells 25 as well as COS-7 cells. 28,36 It is noteworthy that in the Lehman et al, report recombinant PLD2 is shown to co-localize with S6K1 in the perinuclear region. 28 This contradicts the predominant plasma membrane localization of PLD2 observed by others, 69,71 and raises a concern for potential artifact of protein overexpression.…”
Section: Pld1 or Pld2?mentioning
confidence: 96%
“…23,27 However, the mechanism by which PA activates mTOR remains unknown. Curiously, Lehman et al, 28 reported direct binding and activation of S6K1 by PA in vitro, suggesting a route of PA regulation that is independent of mTOR.…”
Section: Phosphatidic Acid and Phospholipase D In Mtorc1 Signalingmentioning
confidence: 99%
“…The two main substrates of mTORC1 are the translational regulators p70 S6 kinase (S6K) and eukaryotic initiation factor 4E-binding protein 1 (4E-BP1), whereas mTORC2 phosphorylates PKB on serine 473. In addition, regulation of the mTORC1 pathway through the binding of the lipid messenger phosphatidic acid (PA) to mTOR [12,13] and S6K [14] has been described. PA is produced through the activity of phospholipase D (PLD) isozymes, among which PLD2 has been shown to be concentration-dependently regulated by oleate [15].…”
Section: Introductionmentioning
confidence: 99%